Interpreting company reports and accounts - Holmes, Geoffrey Andrew; Sugden, Alan (Cambridge : Woodhead-Faulkner, 1975)
"Interpreting Company Reports and Accounts guides the reader through the conventions and complexities of company accounts, explaining how to assess the financial and trading position of a company from year to year, how to spot undue risk taking and 'cosmetic accounting' and where to look for clues on the quality of management."
Includes index.
kjo 15/01/2019
Loans
Keywords: Financial statements; Corporation reports; Corporations--Accounting; Accounting; Great Britain